Upaya Menumbuhkan Jiwa Entrepreneurship melalui Kegiatan Market Day Bagi Anak Usia Dini di Kota Palembang - Igamo, Alghifari Mahdi; Azwardi, Azwardi; Yulianita, Anna; Sari, Dwi Darma Puspita; Marissa, Feny (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Entrepreneurship is increasingly recognized as a crucial factor in economic production, offering solutions in the context of high unemployment rates and limited job opportunities. Developing an entrepreneurial mindset, particularly from an early age, is imperative. This study explores the gradual and strategic nurturing of entrepreneurial spirit, acknowledging that it is a process that unfolds over time, rather than an immediate outcome. In Palembang City, a range of kindergartens serve as fertile grounds for this developmental endeavor. This research focuses on 'Market Day' activities, employed as both a strategy and a pedagogical tool, to stimulate entrepreneurial potentials in early childhood. The effectiveness and impact of these activities on fostering an entrepreneurial mindset among young learners are examined, providing insights into early entrepreneurial education methodologies